Legal Protection Of The Notary In The Production Of A Notarial Deed - Riswadi Riswadi; Rospita Rufina Situngkir (CV. Publikasi Indonesia, 2024)
Along with the development of increasingly modern life, which is characterized by increasing legal relations in written form between fellow citizens, social institutions, and government institutions, the function of a Notary becomes increasingly important, especially in terms of making authentic deeds that can provide legal certainty for the parties. interested parties, parties who receive rights, and their heirs. In other words, as a legal country (rechtstaat), Indonesia is very interested in the existence of professional Notaries. The state's interest in the existence of a professional Notary can be seen in the explanation section of the UUJN, which states the importance of the existence of a Notary, namely related to making authentic deeds. The making of an authentic deed is required by statutory regulations in the context of legal certainty, order, and legal protection for the people who need it. In carrying out his position a notary must be able to act professionally based on a noble personality by always carrying out his duties by the applicable statutory regulations while upholding the notary professional code of ethics as a guideline that must be adhered to. Notaries need to pay attention to what is called professional behavior which has the following elements: (1) having strong moral integrity; (2) being honest with clients and oneself (intellectual honesty); (3) being aware of the limits of their authority; and (4) not based solely on monetary considerations. Article 16 letter a of Law Number 2 of 2014 concerning the Position of Notaries (UUJN) determines that notaries are obliged to act honestly, carefully, independently, impartially, and safeguard the interests of the parties involved in legal actions. In addition, notaries as public officials must be sensitive, responsive, have sharp thinking, and be able to provide appropriate analysis of every legal phenomenon and social phenomenon that arises so that this will foster an attitude of courage in taking appropriate action. The courage referred to here is the courage to carry out correct legal actions by applicable laws and regulations through the deeds that are made and firmly reject the making of deeds that are contrary to law, morals, and ethics. Data analysis was carried out descriptively and qualitatively. Concluding is carried out using a deductive method from general to specific, specifically those related to the research topic, namely Legal Protection of Notaries in Making Notarial Deeds. This research resulted in the finding that Notaries are public officials who, according to Law no. 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning the Position of Notary, hereinafter referred to as UUJN, are given the authority to make authentic deeds regarding all acts, agreements, and stipulations required by statutory regulations and/or as desired. UUJN-P only regulates the provisions for administrative and civil sanctions. However, the Notary's criminal responsibility is imposed if the Notary is proven to have committed a criminal act. If a criminal offense is committed by a Notary, the Notary may be subject to criminal sanctions based on the Criminal Code, while there are several notes that such penalties can be imposed on the Notary.